The Role And Importance Of Investments In The Development Of The National Economy - Khoshimov Jakhongir Ravshanbek ugli (Peerian Journals Publishing, 2023)
The article discloses the content and forms of attracting foreign investment and its role in the development of the economy of Uzbekistan, as well as formulates recommendations and proposals for increasing the attractiveness of the investment environment and actively attracting foreign investment
Keywords: investments; foreign investment; fixed capital; investment environment